The Goldfinch and the Hawk : a Study of Lope de Vega's Tragedy, el Caballero de Olmedo. - McCrary, William Carlton, 1932- (North Carolina Studies in the Romance Languages and Literatures Ser., 2017)
This is a close reading of a play by Felix Lope de Vega (1562-1635)--a Spanish playwright, poet, and major figure of Spanish Baroque literature--titledEl caballero de Olmedo.The study analyzes the comedia in terms of the literary and social conventions that it reflects: cortesia, brujeria, and alcahueteria.